Electrodialysis membrane desalination for water and wastewater processing: irregular attack angles of membranes spacers - Al-Amshawee, Sajjad; Mohd Yusri, Mohd Yunus; Mohamed, Hybat Salih (Springer, 2023)
Electrodialysis desalination is constructed with a number of anion exchange membranes (AEM), cation exchange membranes (CEM), anode, cathode, adjacent silicon gasket integrated membrane spacers, and inlet/outlet holes per cell. At the boundary among an ionic solution and an ion exchange membrane, concentration polarization develops. Spacers placed in between channel’s walls function as stream baffles to increase turbulence, improve heat and mass transfer, diminish the laminar boundary layer, and lessen fouling problems. The current study offers a systematic review of membrane spacers, spacer-bulk attack angles, and irregular attack angles. Spacer-bulk attack angle is accountable for variations in the pattern and direction of stream which impact heat-mass transfer and concentration polarization. Irregular attack angles (e.g., 0°, 15°, 30°, 37°, 45°, 55°, 60°, 62°, 70°, 74°, 80°, 90°, 110°, 120°) in the present study were found to provide unique stream patterns due to the spacer’s filaments being less or more transverse in respect to the primary solution direction, which may significantly alter heat transfer, mass transport, pressure drop, and overall flow dynamics. Spacer applies shear stress resulting by continuous stream tangent to the membrane exterior, which lessens polarization. In the end, 45° is concluded as the preferred attack angle that offers balanced rates of heat transfer, mass transport, and pressure drop throughout the feed channel while greatly lowering the rate of concentration polarization.